2005
DOI: 10.1007/s10832-005-2191-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and Electromechanical Properties of Multimaterial Piezoelectric and Electrostrictive PMN-PT Monomorph Actuators

Abstract: Monolithic multimaterial monomorphs, comprised of varying ratios of piezoelectric 0.65Pb(Mg 1/3 Nb 2/3 )O 3 -0.35PbTiO 3 to electrostrictive 0.90Pb(Mg 1/3 Nb 2/3 )O 3 -0.10PbTiO 3 , have been co-fired at 1150 • C. The relative permittivity, displacement, and polarization hysteresis were investigated for varying ratios of piezoelectric to electrostrictive material. The permittivity of the 1:1 multimaterial monomorphs followed the dielectric mixing laws, showing a dielectric constant of 5,500 at room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The independence on the E Bias polarity indicates the dominant converse piezoelectric effect in PVK‐45 with higher crystallinity . The V‐shaped behavior agrees with the strain change of PMN‐PT substrate under different U Bias (Figure S2, Supporting Information).…”
supporting
confidence: 68%
“…The independence on the E Bias polarity indicates the dominant converse piezoelectric effect in PVK‐45 with higher crystallinity . The V‐shaped behavior agrees with the strain change of PMN‐PT substrate under different U Bias (Figure S2, Supporting Information).…”
supporting
confidence: 68%
“…Recently, Spinks and co‐workers have pioneered another new and important application direction by using CNT fibers as promising electromechanical actuators with the conversion of electrical energy into mechanical energy 5. Compared with other actuation materials such as ferroelectric and electrostrictive materials, conducting polymers, and polymer gels,12–17 the CNT fiber exhibited a unique torsional rotation by a three‐electrode electrochemical system in an electrolyte. A hydrostatic actuation mechanism explained the electromechanical torsion.…”
mentioning
confidence: 99%
“…It has also been reported that the PMN-PT piezoelectric material has better vibration efficiency than PZT materials [13,14]. In a multi-layered actuator, the displacement, ΔT, Fig.…”
Section: Structure Of Pfmtmentioning
confidence: 97%